Language as an instrument of policy - Elena Grinina (Ибероамериканские тетради, 2017)
The purpose of this article is to show how in modern Spain the language is successfully used not only for defending their nationalist interests (linguistic nationalism), but also in the struggle against the structures of language, that reﬂect the gender-based discrimination (linguistic sexism)